2011
DOI: 10.1016/j.jmbbm.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the stick insect antenna: Damping properties and structural correlates of the cuticle

Abstract: Please cite this article as: Dirks, J.-H., Dürr, V., Biomechanics of the stick insect antenna: Damping properties and structural correlates of the cuticle. Journal of the Mechanical Behavior of Biomedical Materials (2011Materials ( ), doi:10.1016Materials ( /j.jmbbm.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 45 publications
8
45
0
Order By: Relevance
“…This is in good agreement with several previous studies, demonstrating the effect of desiccation on the static and dynamic mechanical properties of cuticle from various insect species (Dirks and Dürr, 2011;Klocke and Schmitz, 2011;Mills and Krolak, 1986;Göpfert and Robert, 2001;Schöberl and Jäger, 2006) and other biological composite materials such as bone, squid beaks or even equine hoof walls (Nyman, 2006;Miserez, 2008;Bertram, 1987).…”
Section: Effect Of Water Content On Mechanical Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…This is in good agreement with several previous studies, demonstrating the effect of desiccation on the static and dynamic mechanical properties of cuticle from various insect species (Dirks and Dürr, 2011;Klocke and Schmitz, 2011;Mills and Krolak, 1986;Göpfert and Robert, 2001;Schöberl and Jäger, 2006) and other biological composite materials such as bone, squid beaks or even equine hoof walls (Nyman, 2006;Miserez, 2008;Bertram, 1987).…”
Section: Effect Of Water Content On Mechanical Propertiessupporting
confidence: 93%
“…Over the past 60years, different insect species and body parts have been tested by engineers and biologists, using various techniques, and it has been shown that the Young's modulus of cuticle can range from less than 1kPa (intersegmental membranes of mature female locusts) to several GPa (tendons) (Vincent and Wegst, 2004). It has also been shown experimentally that variations of the cuticle's fibre alignment, water content and controlled 'tanning' of the material affect the cuticle's static mechanical properties, such as stiffness and hardness, and dynamic mechanical properties, such as damping, over several orders of magnitude (Müller et al, 2008;Klocke and Schmitz, 2011;Dirks and Dürr, 2011;Schöberl and Jäger, 2006;Göpfert and Robert, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic response showed no signs of directional anisotropy when comparing dorsal, ventral, lateral and medial planes. This directional isotropy corroborates findings in stick insect antennae (Dirks and Dürr, 2011) and is consistent with our static bending results. The variance in frequencies observed in the present study can mainly be attributed to different initial deflection angles.…”
Section: The Antenna Rapidly Damps Oscillationssupporting
confidence: 93%
“…a decreasing stiffness profile -can help resolve finer details (higher spatial frequencies) during a contour extraction task (Demir et al, 2010). Studies on the biomechanics of arthropod antennae such as in crayfish (Sandeman, 1989) and stick insects (Dirks and Dürr, 2011) are consistent with a decreasing flexural stiffness from base to tip. While from geometry we expect similar mechanical properties in P. americana (Kapitskii, 1984), further mechanical testing will be necessary.…”
Section: Physical Model Of Antenna Provides Insight On Preview Distancementioning
confidence: 94%